The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1002/1521-3773(20000915)39:18<3287::aid-anie3287>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Conformation Control of Oligosilanes Based on Configurationally Constrained Bicyclic Disilane Units

Abstract: The dihedral angles of Si‐Si‐Si‐Si frameworks were controlled to ∼10°(S), 180°(A), and ∼120°(E) by the use of the syn‐ and anti‐disilane units that are configurationally constrained by two pentamethylene tethers. The UV absorption spectra of the tetrasilanes (see picture) were found to be consistent with the new explanation proposed by Michl and co‐workers for the UV absorption of polysilane compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
71
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(75 citation statements)
references
References 14 publications
4
71
0
Order By: Relevance
“…It was shown theoretically and experimentally that the σ-σ* absorption peak shifts dramatically to the red as the SiSiSiSi dihedral angle, ω, is increased from 0° to 180° [99][100][101][102][103][104]. This effect was explained by 1,4-orbital interactions (β vic ), being most effective (maximum orbital overlap) in the HOMO (σ-type orbital) of a syn-conformer, while not present in an anti-conformer.…”
Section: Conformational Effectsmentioning
confidence: 95%
See 1 more Smart Citation
“…It was shown theoretically and experimentally that the σ-σ* absorption peak shifts dramatically to the red as the SiSiSiSi dihedral angle, ω, is increased from 0° to 180° [99][100][101][102][103][104]. This effect was explained by 1,4-orbital interactions (β vic ), being most effective (maximum orbital overlap) in the HOMO (σ-type orbital) of a syn-conformer, while not present in an anti-conformer.…”
Section: Conformational Effectsmentioning
confidence: 95%
“…Perhaps, the most striking example provides a series of conformationally constrained hexasilanes 59-62 (composed of three dihedral angles) that have been structurally characterized by X-ray studies [100,101] (Figure 22). These findings clearly revealed that σ-conjugation in polysilanes is effectively extended by anti or deviant conformations, while conformations with small dihedral angles such as syn, cis or gauche do not contribute to the extent of σ-conjugation [102].…”
Section: Conformational Effectsmentioning
confidence: 99%
“…Furthermore, homocatenated silicon oligomers with conformations (trans, cis, etc.) controlled by introducing bulky substituents have also been synthesized to examine the change in electronic and optical properties caused by σ-conjugation [4].Nanotechnology that can manipulate molecules or polymers has encouraged the development of single molecular conduction using scanning tunneling microscope (STM) analysis [5,6]. The STM-controlled break junction method can measure step-like conductance in molecular samples affixed to the cantilever of the STM system.…”
mentioning
confidence: 99%
“…Furthermore, homocatenated silicon oligomers with conformations (trans, cis, etc.) controlled by introducing bulky substituents have also been synthesized to examine the change in electronic and optical properties caused by σ-conjugation [4].…”
mentioning
confidence: 99%
“…In our recent study on the photophysical properties of conformationally controlled oligosilanes using disilane units configurationally constrained into syn or anti by two pentamethylene tethers ( Figure), 1 we reported the synthesis of the tetrasilane compound anti,anti-dimer 2 (shown in Scheme) by the reaction of syn,syn-1,4-dichlorotetrasilane 1 with methyllithium with inversion of configuration at both silicon centers. 2 Since the yield of this reaction was not satisfactory (30%), we have been trying to optimize the reaction conditions and found the following unprecedented effect by metal cyanides: (1) the yield and the selectivity for 2 are dramatically increased by the addition of potassium cyanide to the reaction mixture, and (2) the stereoselectivity is completely changed from inversion to retention by the change in the countercation of the cyanide salt added, namely from potassium to copper(I).…”
mentioning
confidence: 99%